STUDI KANDUNGAN LOGAM DAN CEMARAN MIKROBIOLOGIS SUMBER AIR TANAH DAN MATA AIR YANG DIGUNAKAN SEBAGAI SUMBER AIR OLEH MASYARAKAT KOTA KUPANG - Muntasir, Muntasir (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Underground water as a source of raw water is used by the people of the city of Kupang in meeting the needs of clean water due to the limited source of surface raw water. Nearly ninety percent of the clean water needs of the people of Kupang City come from groundwater sources. This study aims to describe the study of chemical content and microbiological contamination of water from ground and spring water sources used by the people of Kupang. This research was conducted in the city of Kupang with a sample of 5 points of water sampling by purposive sampling. This type of research is descriptive research with a quantitative approach. The samples were tested chemically using the Atomic Absorption Spectrophotometry method for the determination of metal concentrations and the microbiological method for the determination of microbiological contamination. The results showed that the source of groundwater as raw water used by the community in Kupang City is managed by an individual business entity in the form of CV, UD which is able to produce water from drilling results and distribute it to the community through water tanks of more than 20 cars per day from 5 research sites. Physical requirements including color, odor and taste indicate that all samples of groundwater or drilled water meet the requirements of clean water quality. Chemical examination of water pH meets the requirements, Chemical examination of metal content of Iron is in the range of 0.0720 mg/L – 0.0900 mg/L, Cadmium metal is in the range of 0.0100 mg/L – 0.0130 mg/L, and Zinc metal ranged from 0.0100 mg/L – 0.0338 mg/L. The chemical content of the metal is below the standard of the Ministry of Health regulation. Based on the standard of the Minister of Health No. 416/MENKES/PER/IX/1990 concerning requirements for clean water quality, water that meets the requirements if the water has an iron metal content of 0.3 mg/L, a metal content of 0.005 mg/L of Cadmium metal and a metal content of Zinc (Zn) of 5 mg/L L. it can be ascertained that the metal content in the water sample is below the specified requirements. Examination of the Escherichia coli Bacteria Content of the 5 groundwater sources or drilled wells does not meet the requirements with a percentage of 100%. Bacteriological parameters (Escherichia coli) are said to meet the requirements if, the amount of Escherichia coli content for clean water = 0/100 ml sample. Metal toxicity in humans can cause tissue damage, especially tissue detoxification and excretion (liver and kidney). Some metals have carcinogenic and teratogenic properties. It is necessary to educate and empower the community to use clean water from underground water or drilled water.